THE SYMBIOSIS BETWEEN THE CRIMINALISATION OF SEX WORK AND CORRUPT POLICING IN SEX WORK IN SOUTH AFRICA - Sanger, Cherith (Journal of Anti-Corruption Law, 2023)
Despite existing studies that prove the prevalence of corrupt policing of sex work in South Africa, corruption continues to be a common feature of sex workers’ experiences with police officers. In this article, it is argued that the criminalisation of sex work, which is the current legal model enforced in South Africa, has enabled and cemented corrupt practices in the policing of sex work. Whilst police officers occupy a position of power over all persons living in South Africa, due to their office and authority to enforce the law, it is argued that the police officer/sex worker dichotomy is deepened by the illegal status of the conduct that sex workers engage in. This dichotomy places sex workers in an extremely vulnerable position in relation to police corruption.